Evaluation and metrics framework - Michele Catalano; Gianfranco Giulioni; Werner Streitberger; Michael Reinicke; Torsten Eymann (Universität Bayreuth, Lehrstuhl für Wirtschaftsinformatik, 2005)
In this paper a metrics framework for evaluating different scenarios in the CATNETS project is defined. The aim is to use this framework to compare the catallactic scenario against the central auctioneer.
urn:nbn:de:bvb:703-opus-3629
Keywords: 004; Grid Computing